EFFECT OF SEED RATES AND LEVELS OF ALJAMIEUH LIQUID FERTILIZER ON GROWTH AND YIELD OF BARLEY. - Ali Abed Gatea (European Journal of Agricultural and Rural Education, 2022)
A field experiment was conducted for the barley crop Hordeum vulgare L for the winter season 2019-2020 in a farmer’s field located in Abi Gharq area 10 km west of Hilla Center / Babylon province ,To know (the effect of seed rates and levels of Aljamieuh liquid fertilizer on the growth and yield of barley). A factorial experiment was used by randomized complete block design (R.C.B.D) with three replications (Al-Rawi and Khalaf Allah, 2000).The experiment included two factors, the first factor was concentrations of Aljamieuh liquid fertilizer spray (5,0 and 10) ml. L-1 and which is symbolized by (T0, T1, T2), while the second factor included three seed averages (100, 150 and 200) kg. ha-1,The following which is symbolized by (V1, V2, V3).The results indicated that there were significant differences between the levels of factors in the studied traits, where there was a significant difference between the seed average, where the seed average 150 kg.ha-1 (V2)excelled in some traits, including the number of tillers. m 2, the number of spikes. m 2 and the number of grains. spike -1 by giving it the highest average of (321.33 spikes. m 2, 309.22 spikes. m 2 and 58.55 grains. spike -1 ,While the seeding average of 100 kg.ha-1 (V1) gave the highest average in the plant height. cm and a weight of 1000 grains. g (110.44 cm and 35.33 g).The concentrations of the Aljamieuh liquid fertilizer spray showed significant differences in all the traits included in the study, where the concentration10 ml. L-1 (T2) was given as the highest average of the plant height(cm),number of tillers.m2 , the number of spikes. m2, the number of grains. spike 1- and the weight of 1000 grains. (g) reached (109.00 cm, 320.44 grains. m², 306.77 spikes. m², 55.88 grains and 35.11 g).